Osteoblast response to commercially available demineralized bone matrices - An in-vitro study - Kumaran S; Arun K; Sudarsan Sabitha; Talwar Avaneendra; Srinivasan N (Wolters Kluwer Medknow Publications, 2010)
Objective: Reconstruction of lost attachment apparatus is a major goal of periodontal therapy. Although various osteoinductive bone replacement grafts (BRGs) have been used with apparent clinical success, unequivocal evidence of osteoinductivity may be obtained only through the demonstration of increased osteoblastic/osteoclastic differentiation following exposure to these materials. Materials and Methods: Bone marrow stem cells (BMSCs) obtained from rat femur were cultured in Dulbecco′s Modified Eagles Medium (DMEM) and 10% fetal bovine serum (FBS). They were then exposed to two demineralized bone matrices (DBM′s) - Grafton and Osseograft, and divided into three groups, comprising of a negative control (BMSC + DMEM + 10% FBS), Grafton, Osseograft. An osteogenic medium (OM) (10 hm dexamethasone, 10 hm b-glycerophosphate, and 50 μg/ml ascorbic acid) was added to create three subgroups comprising of a positive control (OM), Grafton with OM, Osseograft with OM. Results: After an initial phase (up to day 5), both Grafton and Osseograft induced an increased proliferative activity in the BMSCs, which reached a plateau after day 10. These grafts also induced increased alkaline phosphatase activity when compared to the control groups and to BMSCs with an OM. Conclusion: Both Osseograft and Grafton are capable of inducing osteoblastic proliferation and differentiation.